Mindset Transformation in School Counseling Services After the Training Program 7 Jurus BK Hebat: A Mixed Method Study - Mulawarman, Mulawarman; Aryani, Farida; Nurfitri, Aldila Dyas; Hilman, Najma Sana Nadhirah; Nadhita, Galuh; Nugraini, Erna Dwi; Prabawa, Abi Fa’izzarahman; Antika, Eni Rindi (Jurnal Kajian Bimbingan dan Konseling, 2026)
School counseling services have shifted from a remedial approach to one of development and prevention, requiring school counselors to possess a reflective and adaptive professional mindset. This study aims to analyze the transformation of counseling mindsets among guidance and counseling teachers after participating in the 7 Jurus BK Hebat training program, as well as to identify supporting and inhibiting factors. Using a mixed methods approach with a convergent design, the study involved 411 participants selected through convenience random sampling. Data were collected using a mindset transformation scale (α = .939) and open-ended questionnaires, then analyzed descriptively and thematically. The findings are expected to illustrate mindset change patterns and inform sustainable reflective training models.